The Impact of COVID-19 & Safer-at-Home Policies on US Public Transit - Islam, Anik (Université d'Ottawa | University of Ottawa, 2020)
COVID-19 has affected travel behavior and disrupted public transit usage. This paper investigates the short-term impact of COVID-19 and safer-at-home policies on public transit ridership and vehicle usage in the US. Using monthly data from the National Transit Database between January 2012 and June 2020, this paper finds that ridership has decreased by 67 to 71 percent. Similarly, vehicle usage in terms of number of hours and miles travelled has decreased by 43 to 45 percent and 46 to 48 percent respectively post the incidence of COVID-19. Interestingly, there is heterogeneity in terms of ridership across different modes of transport. Smaller modes faced greater decrease in ridership, while ‘demand driven’ modes experience increase in ridership. Using variation in implementation of safer-at-home policies across states, this paper also finds that these policies did not cause a statistically significant decrease in public transit ridership and vehicle usage. The findings and the possible policy implications are briefly discussed.